Biocompatible hydrogelators based on bile acid ethyl amides - Kuosmanen, Riikka; Puttreddy, Rakesh; Willman, Roosa-Maria; Äijäläinen, Ilkka; Galandáková, Adéla; Ulrichová, Jitka; Salo, Hannu; Rissanen, Kari; Sievänen, Elina (Steroids, 2016)
Four novel bile acid ethyl amides were synthetized using a well-known method. All the four compounds were characterized by IR, SEM, and X-ray crystal analyses. In addition, the cytotoxicity of the compounds was tested. Two of the prepared compounds formed organogels. Lithocholic acid derivative 1 formed hydrogels as 1% and 2% (w/v) in four different aqueous solutions. This is very intriguing regarding possible uses in biomedicine.
Keywords: Mice; biokompatibilní materiály; Models, Molecular; Biocompatible Materials; kyselina lithocholová; Amide; Lithocholic Acid; myši; amidy; Hydrogels; Bile acid; molekulární modely; voda; Self-assembly; 3T3 Cells; hydrogely; molekulární konformace; Molecular Conformation; Water; Biocompatibility; Supramolecular hydrogel; buňky 3T3; Animals; zvířata; Amides